2015
DOI: 10.1108/intr-02-2014-0053
|View full text |Cite
|
Sign up to set email alerts
|

Roles of perceived value and individual differences in the acceptance of mobile coupon applications

Abstract: Purpose -The purpose of this paper is to examine how consumers' value evaluation and personality factors influence consumers' intention to adopt mobile coupon (M-coupon) applications in China. The moderating effect of gender on the relationships between personality factors and consumers' adoption intention is also tested. Design/methodology/approach -This study conducted a survey to collect data from M-coupon application users. In total, 271 valid responses were analyzed using structural equation modeling (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
141
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 72 publications
23
141
2
8
Order By: Relevance
“…Perceived value concept helped in explaining consumers decision making behaviors for years. Also many studies use perceived value and technology adoption relation to explain better understanding consumer technology adoption (Turel, Serenko & Bontis, 2007;Kim, Chan & Gupta, 2007;Kleijnen, De Ruyter & Wetzels, 2007;Liu, Zhao, Chau & Tang, 2015). Turel et al (2007) stated that perceived value can be used to explain the consumer technology adoption in connection with the cognitive structure of technology adoption.…”
mentioning
confidence: 99%
“…Perceived value concept helped in explaining consumers decision making behaviors for years. Also many studies use perceived value and technology adoption relation to explain better understanding consumer technology adoption (Turel, Serenko & Bontis, 2007;Kim, Chan & Gupta, 2007;Kleijnen, De Ruyter & Wetzels, 2007;Liu, Zhao, Chau & Tang, 2015). Turel et al (2007) stated that perceived value can be used to explain the consumer technology adoption in connection with the cognitive structure of technology adoption.…”
mentioning
confidence: 99%
“…Danaher et al (2015) showed that face value, distance, and perceived convenience were factors affecting redemption. Liu et al (2015) found that perceive value, coupon proneness, and personal innovativeness positively influence the intention to redeem digital coupons whereas perceived risk negatively influences it. In addition to above factors, the present study considers important new variables such as intention to search and consumption frequency, which also play a role in coupon redemption.…”
Section: Discussionmentioning
confidence: 97%
“…Clark et al (2013) have used theory of reasoned action (TRA) to explain digital coupon redemption behaviour. Liu et al, (2015) have used unified theory of acceptance and use of technology (UTAUT) theory to explain consumer's redemption intention for digital coupons. The TPB model of digital redemption advances the TRA model by including perceived behaviour control as a third antecedent predicting coupon redemption intention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations